XONAKILASHTIRILGAN QUSHLARNING INSON HAYOTIDAGI AHAMIYATI - Ruiddinov , A. (Educational Research in Universal Sciences, 2023)
Domesticated birds are important in human life. People use them to get meat, eggs, feathers. Examples of domesticated birds are chickens, turkeys, geese, ducks, pigeons, and grouse. The origin, ecological and biological characteristics of these birds are mentioned below.